The Role of Women in Community Development: Reenacting Digital Activism in Improving Education for All Children, Lesson Learned from Tulungagung and Semarang - Anggraheni, Palupi; Fatharini, Anjani Tri; Nurhaqiqi, Hanna; Mustikasari, Ratih Pandu; Diaz, Yohana Grezia; Gultom, Miracle Nauli (JURNAL SOSIAL HUMANIORA (JSH), 2024)
Women have a significant role in ensuring the continuity of teaching and learning activities in both the formal and non-formal sectors, particularly regarding digital literacy challenges in early childhood education (3-6 years old). Especially considering the increased need for digital skills during and after COVID-19. The potential for gadget addiction and abuse that leads to online-based violence encourages the important role of the community in aligning challenges as well as opportunities for digitalization of early childhood education. Aligned with SDGs number 4 concerning quality education. This research seeks for the red thread of the role of women as agents in the development of community-based early learning methods, especially the implementation of digital literacy. Primary data was taken from focus discussion group extraction, curriculum development, and joint monitoring-evaluation on digital literacy, which was held at MI Muhammadiyah Junjung, Tulungagung Regency and Komunitas Harapan on the Johar Market Riverside, Semarang. The concepts of Women in Development and Digital Literacy empowers women to contribute to development, cybersecurity, and children's rights. The results highlight structural issues like poverty and gender inequality as barriers to educational quality across regions, further emphasizing the need for women educators in designing digital literacy programs.